1991
DOI: 10.1002/jso.2930470213
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholangiocarcinoma in hepatolithiasis: A frequently overlooked disease

Abstract: Five cases of intrahepatic cholangiocarcinoma were found among 101 cases of hepatolithiasis. There was no definite sign of cholangiocarcinoma in ERCP and image studies of four cases. The possibility of the existence of occult cholangiocarcinoma should be kept in mind, especially when unusual presentations, such as body weight loss, anemia, palpable abdominal mass, and intractable pain, appear. An intraoperative frozen-section examination should be considered under the following circumstances: (1) whitish nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…Hepatolithiasis are gallstones located in the intrahepatic bile ducts, which is an established risk factor for CCA. The incidence of IH-CCA in patients with hepatolithiasis is reported to be 4-11% [39]. CCA development in patients with hepatolithiasis is very likely caused by recurrent cholangitis and chronic inflammation of the biliary epithelium [40].…”
Section: Cholelithiasismentioning
confidence: 99%
“…Hepatolithiasis are gallstones located in the intrahepatic bile ducts, which is an established risk factor for CCA. The incidence of IH-CCA in patients with hepatolithiasis is reported to be 4-11% [39]. CCA development in patients with hepatolithiasis is very likely caused by recurrent cholangitis and chronic inflammation of the biliary epithelium [40].…”
Section: Cholelithiasismentioning
confidence: 99%
“…9 However, in cholangiocellular carcinoma some drawbacks of ERCP are known. 10,11 As ERCP was non-diagnostic an intrahepatic nature of the icterus was assumed necessitating a histologic diagnosis. A transjugular biopsy was performed because this method has proved to be a useful technique particularly in patients after BMT 12 because of minimising the bleeding hazard due to thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the problem of the concomitant occurrance of intrahepatic stones with cholangiocarcinoma. It has been reported that, in 5.0-8.7% [16][17][18] of the patients, intrahepatic stones were concomitant with cholangiocarcinoma. Chronic prolifer ative cholangitis in the presence of intrahepatic stones could undergo progressive changes to atypical epithelial hyperplasia, which might in turn progress to cholangio carcinoma [19].…”
Section: Discussionmentioning
confidence: 99%